Calcifediol supplementation to reduce pulse pressure in a limited sample of vitamin D deficient older adults with elevated parathyroid hormone levels. (April 2019) - Grootswagers, Pol; Vaes, Anouk M.M.; Tieland, Michael; de Groot, Lisette C.P.G.M.
Summary: Vitamin D is proposed as an antihypertensive agent, but current evidence is inconclusive. Calcifediol is more potent in raising vitamin D status. It might, therefore, be more effective in lowering pulse pressure than cholecalciferol especially in patients with low vitamin D status and high levels of parathyroid hormone (PTH). This study investigated the efficacy of calcifediol on pulse pressure in older adults with vitamin D deficiency and elevated PTH levels. Supplementation with 15 μg calcifediol resulted in lower pulse pressure (Δ 35.4 mm Hg, 95%CI: 4.8, 66.1 mm Hg, P = 0.021) and PTH levels (Δ 1.83 pmol/l, 95%CI: −0.1, 3.7 pmol/l, P = 0.065) compared to 5 μg calcifediol. These effects were observed in a limited sample size of 16 older adults and therefore need confirmation in a larger trial. In conclusion, supplementation with 15 μg calcifediol might be an effective way to reduce pulse pressure in elderly with vitamin D deficiency and elevated PTH levels.